Juridical Analysis of Child Custody Disputes Involving Parents with Psychological Disorder - Destya Anggraeni; Sulastri Sulastri (Law Development Journal, 2025)
Child custody disputes following divorce in Indonesia continue to leave broad interpretive gaps and contribute to legal uncertainty. This study examines post-divorce child custody conflicts with a particular focus on cases involving parents with psychological disorders. The research employs a normative legal method through an analysis of statutory regulations and judicial decisions. Child custody in Indonesia is governed by the Marriage Law, the Compilation of Islamic Law (KHI), and the Child Protection Law, all of which consistently emphasize the principle of the best interests of the child. However, in practice, significant legal uncertainty remains, as judges often rely primarily on Article 105 of the KHI, which grants custody of non-mumayyiz children or those under the age of twelve to the mother, even when she exhibits psychological disorders. The case studies examined in this research Decision No. 4222/Pdt.G/2023/PA.Tgrs and Decision No. 0461/Pdt.G/2020/PA.Gs demonstrate differing judicial considerations in assessing evidence of psychological disorders. The findings highlight the need for a more comprehensive judicial approach and standardized psychological assessment procedures for both children and parents in custody disputes, ensuring decisions are more objective and child-protection oriented. Such measures are expected to prevent children from becoming victims of custody conflicts and to safeguard their long-term well-being.